Reconstructing prehistoric lifeways using multi-Isotope analyses of human enamel, dentine, and bone from Legaire Sur, Spain. - Jacob I Griffith; Hannah F James; Javier Ordoño; Teresa Fernández-Crespo; Carina T Gerritzen; Christina Cheung; Rachèl Spros; Philippe Claeys; Steven Goderis; Barbara Veselka; Christophe Snoeck (PLoS ONE)
Megalithism has been repetitively tied to specialised herding economies in Iberia, particularly in the mountainous areas of the Basque Country. Legaire Sur, in the uplands of Álava region, is a recently excavated passage tomb (megalithic monument) that held a minimum number of 25 individuals. This study analysed the carbon, nitrogen, oxygen, and strontium isotope ratios of 18 individuals, in a multi-tissue sampling study (successional tooth enamel sampling, incremental dentine sampling, and bulk bone collagen sampling). The results provide a high-resolution reconstruction of individual mobility, weaning, and dietary lifeways of those inhumed at the site. Oxygen and strontium isotope analysis suggest all individuals come from a similar, likely local, geological region, aside from one biological female who presents a notably different geographical birthplace, weaning, and dietary life history than the rest of the burial population. Comparisons to other nearby megalithic sites (∼35km as the crow flies), located in a valley area, reveal that, whilst sharing the same mortuary practices, these individuals held notably different lifeways. They highlight notably earlier ages of cessation of nursing (≤2 years at Legaire Sur vs. ≥4 years in other megalithic tombs), and a greater dependence on pastoralism than previously observed in lowland megalithic graves. The results from Legaire Sur reveal the complexity of the Late Neolithic-Chalcolithic transition in north-central Iberia, categorising yet another separate socio-economic group with distinctive lifeways inhabiting the region.